Hypothyroidism and Its Comorbidities - An Observational Study at A General Hospital - Bodiuzzaman, MM (KYAMC Journal, 2022)
Background: Hypothyroidism is the most common metabolic disorder that slows metabolism and leads to many medical conditions like diabetes (DM) and its complications like hypertension (HTN) and ischemic heart disease (IHD). Objectives: This study was conducted to determine the prevalence of various comorbidities in the hypothyroid population, to compare them, and to demonstrate that we can prevent those comorbidities through early detection and treatment of primary diseases such as hypothyroidism. Materials and Methods: An observational study was conducted in a general hospital in Faridpur from October 2019 to December 2020 for a period of one year and three months. A total of 170 hypothyroid patients were selected randomly from all sexes and races to see their comorbidities. Clinically suspicious patients were selected for laboratory testing and, after confirmation of hypothyroidism, comorbid conditions were searched for by clinical examination and biochemical tests where needed. All new and old patients were included as cases in this study. Result: 170 cases were selected as hypothyroidism out of a total of 3233 patients (5.25%). Female patients were more than male cases (134 vs. 36 and a ratio 3.2:1). More patients were above 50 years (29.41%). Comorbidities present most of the patients (88.82%). Most common comorbidities were HTN, DM, BA, and IHD (40%, 19.41%, 14.11%, and 11.76%, respectively). Common concomitant comorbidities were HTN with DM (15.23%) and HTN with IHD (11.25%). Conclusion: There is a high incidence of HTN, DM, BA, and IHD in association with hypothyroidism. Overt hypothyroid patients are more likely to suffer from HTN and DM. As a result, these comorbid conditions should be investigated in all hypothyroid patients. KYAMC Journal. 2022;12(04): 222-225